DEPRESSIVE SYMPTOMS AMONG FAMILY MEMBERS PROVIDING INFORMAL CARE FOR PATIENTS RECEIVING HOME-BASED CARE: A PHQ-9 CROSS-SECTIONAL STUDY - Gavrilović, Nikola (Srpski medicinski časopis Lekarske komore, 2026)
Introduction/Objective: Family members providing informal care for patients receiving home-based care represent a population at increased risk of developing depressive symptoms. The aim of this study was to assess the presence and severity of depressive symptoms using the PHQ-9 questionnaire and to examine the association between depressive symptoms and caregivers’ daily functioning.Methods: A descriptive-analytical cross-sectional study was conducted among 77 family caregivers of patients enrolled in the Home Care Service of the Health Center Subotica between March and September 2025. Depressive symptoms were assessed using the Patient Health Questionnaire-9 (PHQ-9). Statistical analysis included the t-test, Mann–Whitney U test, Kruskal–Wallis test, and Spearman’s correlation coefficient.Results: The mean PHQ-9 score was 8.48 ± 6.14. A score ≥ 10 was recorded in 30 (38.9%) participants. Minimal or mild depressive symptoms were present in 47 (61.1%) caregivers. No statistically significant differences in PHQ-9 scores were observed according to caregiver sex (p = 0.423) or the patient’s primary diagnosis (p = 0.183). In the overall sample, a statistically significant weak positive correlation was found between PHQ-9 score and the self-reported impact of symptoms on daily functioning (r = 0.294; p = 0.009).Conclusion: Depressive symptoms are present in a substantial proportion of family caregivers providing home-based care. The intensity of depressive symptoms is associated with greater impairment in daily functioning, highlighting the importance of systematic monitoring of caregivers’ mental health.
Keywords: family caregivers; depression; dementia; neoplasms; stroke; screening